2013
DOI: 10.1177/0022466913475872
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Preference Relative to Teacher Implementation of Intervention

Abstract: The purpose of this study was to conduct a preference trial as a preliminary test of preference effects on teacher behavior relative to implementation (adoption, adherence, quality). Teachers were randomly assigned to "preference" or "nopreference" groups and then trained to implement the intervention. Direct observation occurred immediately after initial training, after 6 weeks of coaching support, and after 4 weeks of no support. Results showed that, when compared with the no-preference group, teachers who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…Finally, features of the PD itself may affect the inner narratives teachers develop and future implementation. For example, in a randomized controlled trial, Johnson et al (2014) compared the implementation of the Good Behavior Game (GBG; Barrish, Saunders, & Wolf, 1969) between teachers charged with implementing the GBG and teachers who had the choice of implementing the GBG or another classroom management strategy. Although both groups received equivalent trainings on GBG implementation, the group that chose to implement the GBG had significantly greater treatment integrity ( M = 70%) at the outset of the study compared with the group that did not choose to implement the GBG ( M = 35%).…”
Section: Beliefs Buy‐in and Teacher Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, features of the PD itself may affect the inner narratives teachers develop and future implementation. For example, in a randomized controlled trial, Johnson et al (2014) compared the implementation of the Good Behavior Game (GBG; Barrish, Saunders, & Wolf, 1969) between teachers charged with implementing the GBG and teachers who had the choice of implementing the GBG or another classroom management strategy. Although both groups received equivalent trainings on GBG implementation, the group that chose to implement the GBG had significantly greater treatment integrity ( M = 70%) at the outset of the study compared with the group that did not choose to implement the GBG ( M = 35%).…”
Section: Beliefs Buy‐in and Teacher Behaviormentioning
confidence: 99%
“…School‐based consultation studies have found that many teachers significantly decrease behavior intervention fidelity after outside support has ended (Noell et al, 2000). For example, Johnson et al (2014) found that teachers' treatment integrity decreased from 66% to 36% four weeks after coaching ended. Stormont, Reinke, Newcomer, Marchese, and Lewis (2015) reviewed studies incorporating performance feedback for teacher use of PBM and found that only 28% collected follow up data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Chorpita et al, 2015, p. 79). Educators allowed to select a practice consistent with their preferences adopted the intervention more rapidly, implemented the intervention with greater fidelity, and were more likely to sustain the intervention than the non-preference group (Johnson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Participants' ratings of acceptability are important to highlight because there is evidence that educators will more quickly adopt and while in the absence of coaching, maintain new teaching practices for longer when those teaching practices are preferred (Johnson et al, 2014). On average, participants liked to use, thought they were effective, and would recommend selfmonitoring and BSP to other educators.…”
Section: Discussionmentioning
confidence: 99%